071 Motor network remodelling in ALS and PLS. Issue 6 (27th May 2022) - Edmond, Evan; Proudfoot, Malcolm; Menke, Ricarda; Thompson, Alexander; Talbot, Kevin; Stagg, Charlotte; Turner, Martin
Abstract : Background: Primary motor cortex hyperexcitability demonstrated in amyotrophic lateral sclerosis (ALS) is associated with wider network dysfunction. The precise topology and nature of these functional altera- tions remains unclear, including the extent of overlap between ALS and the pure upper-motor-neurone phenotype - primary lateral sclerosis (PLS). Methods: Study participants comprised 41 ALS, 7 PLS, and 18 age matched healthy individuals. Partici- pantsunderwent motor task functional MRI (fMRI) of the brain at 3T (Siemens Magnetom). The task involved unilateral finger response (Go) to a directional visual cue with intermittent response inhibition (NoGo). Image preprocessing, voxelwise statistics with general linear modelling, and exploratory network analysis were performed using FSL (FMRIB software library). Results: A bilateral pattern of activation was observed with finger movement in the ALS group, compared to the more restricted contralateral hemispheric activity in healthy controls (n.s. after stringent voxelwise multiple-comparison correction). Significantly increased activation was noted in the posterior insula in PLS patients during successful response inhibition compared to both ALS patients and healthy control. Network analysis demonstrated a significant positive association of increasing disability with pre-motor and supplementary motor nodes. Discussion: Regional brain motor network remodelling in ALS may signify degeneration of inhibitory local circuit functional partitioning, or reflect adaptation and mobilisation of reserves to support motor execution. Replication and validation through standardised imaging protocols and task design offers the potential to refine targets for therapeutic neuromodulation. eedmond@gmail.com|NIHR Bursary